The Influence of Leadership Style And Work Culture on Teacher Performance (Study Of Teachers at Sma Negeri 24 Bandung) - Rahmawati, Sovi; Jusdijachlan, R; Ridwan, S (Greenation International Journal of Engineering Science, 2024)
The aim of this research is to determine and analyze: (1) Leadership Style (2) Work Culture; (3) Teacher Performance; and (4) The influence of leadership style and work culture on teacher performance at SMAN 24 Bandung City, both simultaneously and partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is employees in the SMAN 24 Bandung City environment with a sample of 56 people. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that the leadership style at SMAN 24 Bandung City is good, the work culture at SMAN 24 Bandung City can generally be said to be good, the current performance of SMAN 24 Bandung City is considered good. Leadership Style and Work Culture simultaneously influence the performance of SMAN 24 Bandung City. However, partially the dominant Leadership Style influences Performance rather than Work Culture. Because work culture predominantly influences performance, being the first priority in improving performance, SMAN 24 Bandung City is expected to consistently maintain current work habits and culture, so that they are able to work more professionally.